Meaning Making Following Trauma - Park, Crystal L. (Frontiers in Psychology, 2022)
The meaning making model provides s a useful framework for integrating myriad existing meaning-related theories and empirical findings. In this overview, I describe this model, which comprises both global and situational (event-specific) aspects. Global meaning encompasses foundational beliefs, values and goals, and a subjective sense of meaningfulness while situational meaning entails the appraisal of an experience. When an experience is perceived as discrepant with global meaning, individuals experience distress and engage in a variety of efforts to make meaning of that experience. Meaning making is usually aimed at changing the meaning of the situation but can also involve changing global meaning (e.g., adopting a new way of understanding the world or new goals) (i.e., meaning made). Successful meaning making reduces discrepancies between global meaning and individuals’ assigned meaning of the specific experience and restores harmony within their global meaning vis-à-vis their current experience.